Performance evaluation of China's air routes based on network data envelopment analysis approach. (August 2016) - Shao, Yanmin; Sun, Changfu
Abstract: Air routes are among the most important elements of civil aviation transport. Airlines' operations are mainly dependent on the structure and layout of air routes. This paper first divides the production process of air routes into two stages, allocation and transport, based on air route operational characteristics. Then, two network data envelopment analysis (DEA) models are proposed to analyze the efficiency of the system, allocation, passenger transport, and freight transport of 477 air routes. The research result demonstrates that the different constraints on intermediate measure in the network DEA models do affect the air routes' efficiency significantly; Most air routes have high allocation efficiency and passenger transport efficiency, while they have low freight transport efficiency. Furthermore, the efficiencies of 82 airports are also analyzed after aggregating the efficiencies of the air routes. Highlights: Two network DEA models are proposed to analyze the efficiencies of 477 air routes. The constraints of intermediate measure in network DEA models do affect the air route's efficiencies significantly. Most air routes have high allocation efficiency and passenger transport efficiency. Efficiencies of 82 airports are also analyzed after aggregating the efficiencies of the connecting air routes.